2013
DOI: 10.1108/17566261311328855
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities or obstacles?

Abstract: Purpose-Applying theories of entrepreneurship, the paper aims to identify the factors-with theoretical explanations-that act as barriers to migrant women entrepreneurs (MWEs), particularly women from developing countries starting businesses in developed economies. The paper further seeks to explore which barriers also have the potential to act as enablers. Design/methodology/approach-The relationship between immigration, ethnicity, gender and entrepreneurship has received little theoretical attention. Linking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 41 publications
2
31
0
7
Order By: Relevance
“…We hypothesize that a supportive environment influences the relationship between gender and immigrant entrepreneurship in such a way that particularly benefits immigrant women. In line with previous research (Vaccarino et al 2011;Azmat 2013), we argue that immigrant women are in a disadvantaged position and that they are therefore more dependent on a supportive environment. Accordingly, a supportive environment should promote entrepreneurship among immigrant women.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…We hypothesize that a supportive environment influences the relationship between gender and immigrant entrepreneurship in such a way that particularly benefits immigrant women. In line with previous research (Vaccarino et al 2011;Azmat 2013), we argue that immigrant women are in a disadvantaged position and that they are therefore more dependent on a supportive environment. Accordingly, a supportive environment should promote entrepreneurship among immigrant women.…”
Section: Introductionsupporting
confidence: 92%
“…The individual level comprises immigrants' gender, age, cultural background, and human, financial, and social capital. The contextual level includes the host country's economic, social, and political-institutional environment, such as market conditions, governmental support, and regulations (Kloosterman and Rath 2001;Kloosterman 2003;Azmat 2010Azmat , 2013Peroni et al 2016).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite calls for contextualisation and comparative research (Chalmers and Shaw, 2017; Lang et al, 2014; Welter, 2011), we have not found any analyses of copreneurs that address country comparisons. Country context including normative regimes, historical and contemporary economic conditions, and social policy shape conditions for doing business and surrounding discourses (Azmat, 2015; Korpi et al, 2013; Zahra et al, 2014). Comparative copreneurship research represents a unique and focused environment to study differing dynamics of business-family embeddedness.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging literature on women entrepreneurs focuses on different aspects and dimensions, arguing from different theoretical backgrounds and using different methodological approaches. Nevertheless, some important strands of literature can be identified concerning different areas of investigation: First, there is an immanent focus on obstacles that migrant women entrepreneurs face due to gender, their status in the host society, and/or their 'ethnicity' influencing, for example, networking, access to resources, and human and social capital (Azmat 2013;Baycan-Levent 2010;Pio 2007;Erel 2010). Second, studies analyse whether women's self-employment leads to empowerment and integration or is primarily a reaction to labour market discrimination (Apitzsch 2003;Morokvasic 1991).…”
Section: Who Is a Migrant Or 'Ethnic' Entrepreneur?mentioning
confidence: 99%